(untitled) (Global Conference on Medical and Health Sciences, 2026)
Dysregulation of the autonomic nervous system (ANS) plays a critical role in the pathophysiology of numerous neurological disorders, including stroke, Parkinson’s disease, multiple sclerosis, and traumatic brain injury. Traditionally, heart rate variability (HRV) has been the primary non-invasive biomarker used to assess autonomic function. However, HRV alone may not fully capture the complexity of autonomic imbalance, particularly in the context of central nervous system dysfunction. Emerging evidence suggests that a broader range of physiological signals—such as electrodermal activity, baroreflex sensitivity, pupillometry, and neurocardiac coupling—can provide deeper insights into autonomic regulation.